Statistical Guideline #7 Adjust Type 1 Error in Multiple Testing. - Liu, Ren (International Journal of Behavioral Medicine, 2022)
This is one in a series of statistical guidelines designed to highlight common statistical considerations in behavioral medicine research. The goal is to briefly discuss appropriate ways to analyze and present data in the International Journal of Behavioral Medicine (IJBM). Collectively, the series will culminate in a set of basic statistical guidelines to be adopted by IJBM and integrated into the journal's official instructions for authors, and to serve as an independent resource. If you have ideas for a future topic, please email the Statistical Editor, Ren Liu at rliu45@ucmerced.edu.